PLAN-M; Mycobacteriophage Endolysins Fused to Biodegradable Nanobeads Mitigate Mycobacterial Growth in Liquid and on Surfaces - Davies, Courtney G.; Reilly, Kerri; Altermann, Eric; Hendrickson, Heather L. (Frontiers in Microbiology, 2021)
The global increase in multiple drug-resistant pathogens, in combination with an absence of new antibiotics, has led to a deepening interest in how bacteriophages (phages) and phage-based strategies can be used to combat pathogens. The Mycobacteria are a genus of Actinobacteria that include human pathogens such as Mycobacterium tuberculosis (TB), which generally infects the lungs and can persist as a latent or active infection. While drug cocktails and treatment for TB exist, infected patients with active TB disease can spread the disease to healthcare workers and to their community. The HHMI SEA-PHAGES program (https://seaphages.org/) has contributed to discovering and documenting bacteriophages that are able to infect M. smegmatis MC2 155, a close relative of M. tuberculosis, in the phagesdb database (https://phagesdb.org). This well-documented collection of diverse Mycobacteriophages is an excellent resource for trialling bacteriophage-sourced enzymes in novel applications. Previous work suggests that the LysB enzyme from Mycobacteriophage D29 can lyse M. smegmatis MC2 155 cells from without. We therefore set out to explore the ability of this and other Mycobacteriophage endolysins to lyse their host strain when they are attached to biodegradable polyhydroxyalkanoate (PHA) nanobeads. We selected the sequences of two LysA and six LysB gene homologs from the phagesdb collection to be fused to the polyhydroxyalkanoate synthase C (phaC) by being co-expressed and displayed on the surface of functionalised PHA nanobeads. Lysins thus directionally displayed on nanobeads were able to rupture M. smegmatis MC2 155 cells from without, causing up to 0.79 cell death in standing liquid tests and 0.91 cell death in a standard antibacterial fabric assay. In our hands LysB enzymes performed better than the LysA enzymes in fabric assays. These results suggest that bacterial endolysins, and particularly LysB enzymes, are stable and active when displayed on PHA nanobeads. Our results provide the proof-of-principle that Mycobacteriophage endolysins can be used independently of the virus particles, and, when applied as functionalised nanobeads, protect surfaces that come into contact with aerosolised bacteria.